Sistem Informasi Reservasi Homestay Berbasis Web Dengan Metode End-User Development Pada Arinta House Depok - Ridhwan Ramadhan (CV. Multi Kreasi Media, 2024)
The problem experienced by guests who want to stay at Arinta house is the room reservation process where prospective inmates must come directly to the Arinta house reception so it is less effective to find out whether or not there is an empty room, and the manual data input process often causes errors in the data collection process. . If the data to be processed is large, it will experience difficulties and errors that occur because of the lack of accuracy of the recorder. This research was made using the End-User Development method and the analysis was carried out by interviewing and surveying the current system and collecting data to obtain the required information. The process design method focuses on developing models using UML (Unified Modeling Language) such as Use Case Diagrams, Sequence Diagrams, Activity Diagrams and Class Diagrams. The result of applying the method in designing a web-based Homestay reservation information system is that it can simplify the process of developing and documenting applications from the beginning to the creation of an application. So that it can help the company in providing the best service for the innkeepers as well as simplify and speed up the services provided to guests who want to stay.